Guiding, bending, and splitting of coupled defect surface modes in a surface-wave photonic crystal - Gao, Zhen (2016)
We experimentally demonstrate a type of waveguiding mechanism for coupled surface-wave defect modes in a surface-wave photonic crystal. Unlike conventional spoof surface plasmonwaveguides, waveguiding of coupled surface-wave defect modes is achieved through weak coupling between tightly localized defectcavities in an otherwise gapped surface-wave photonic crystal, as a classical wave analogue of tight-binding electronic wavefunctions in solid state lattices. Wave patterns associated with the high transmission of coupled defectsurface modes are directly mapped with a near-field microwave scanning probe for various structures including a straight waveguide, a sharp corner, and a T-shaped splitter. These results may find use in the design of integrated surface-wave devices with suppressed crosstalk.